Globalisation: countries, cities and multinationals - Philip McCann; Zoltán J. Ács (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
In this paper we explore the relationship between the size of a country, the size of its cities, and the economic performance of the country. In order to do this we integrate three different literature, namely the literature on optimal country size, literature on historical processes of urbanisation and the performance of cities, and literature on the role of multinational firms in the global economy. Using an economic geography perspective, we demonstrate that the relationship between city-size and the prosperity of the nation state, to a much more complex set of relationships. In the modern era of globalisation the role of global companies within the city-region is critical, and city-regions in turn are seen to drive national economies. As such, the relationships between firms, cities and countries have been largely reversed, casting doubt on various institutional economic theories.
Keywords: R12; F23; N90; O33; 330; scale; cities; countries; multinational firms; globalisation; Produktivität; Landesgröße; Stadtgröße; Multinationales Unternehmen; Standortwettbewerb; Globalisierung; Welt; OECD-Staaten